Assessing Translator Education in the Light of Competency-Based Approaches: Dashboard Indicators and Stakeholders’ Sense-Making - Sakwe George Mbotake (International Journal of English Language and Translation Studies, 2017)
The effect of globalization and the increasing demands on the job market have induced many countries in the world to introduce reforms aimed at streamlining their higher education curricula. The demand for a more flexible workforce with high skills (competencies) in problem solving, team work and project management has been on the rise in recent years and the incorporation of competency-based curriculum has emerged as a necessity in the higher education sector. However, in spite of the growing popularity for the need to prepare graduates for the workplace, the actual academic culture and formative processes are yet to be tailored to address these new exigencies. The aim of this paper is to analyze in what manner competence and competence-based learning are being currently implemented in the Advanced School of Translators and Interpreters (ASTI) of the University of Buea in Cameroon. Competency dashboard indicators from best practice frameworks are used to assess stakeholders’ sense-making as levers for quality assessment in translation learning. An opinion survey of 60 trainee translators and 12 instructors helped to identify factors, instructional and otherwise which promote or inhibit the success of competence-based education. The study posits that systemic and environmental issues, as well as organizational, teaching and learning, assessment, and quality assurance issues are germane to the effective implementation of generic and specific competencies. The ensuing proposals advocate for a responsive translator training and education that is more personalized and adaptive to address higher education’s challenges of access, quality, and affordability for a diverse set of students.